INTEGRATING OUTCOME-BASED EDUCATION IN TRADITIONAL DANCE CURRICULUM: A CASE STUDY OF SUNDA DANCE IN HIGHER EDUCATION - Utami Arsih; Putri, Rimasari Pramesti; Aesijah, Siti; Pebrianti, Sestri lndah (Acintya, 2024)
This research aims to integrate the Outcome-Based Education (OBE) approach in the curriculum in higher education, especially Sundanese dance courses. This approach is designed to increase the relevance of learning outcomes to the needs of society and the world of work. This study uses a descriptive qualitative method with a case study approach in the Dance Education Study Program, Faculty of Languages ​​and Arts, Semarang State University. The research results show that the application of OBE in Sundanese dance learning can strengthen student competence, both in terms of technical skills and ability to adapt to global challenges.